Policy Risk and the Business Cycle - Benjamin Born; Johannes Peifer (University of Bonn, Bonn Graduate School of Economics (BGSE), 2011)
The argument that policy risk, i.e. uncertainty about monetary and fiscal policy, has been holding back the economic recovery in the U.S. during the Great Recession has a large popular appeal. We analyze the role of policy risk in explaining business cycle fluctuations by using an estimated New Keynesian model featuring policy risk as well as uncertainty about technology. We directly measure uncertainty from aggregate time series using Sequential Monte Carlo Methods. While we find considerable evidence of policy risk in the data, we show that the "pure uncertainty"-effect of policy risk is unlikely to play a major role in business cycle fluctuations. With the estimated model, output effects are relatively small due to i) dampening general equilibrium effects that imply a low amplification and ii) counteracting partial effects of uncertainty. Finally, we show that policy risk has effects that are an order of magnitude larger than the ones of uncertainty about aggregate TFP.
Keywords: E32; E63; C11; 330; Policy Risk; Uncertainty; Aggregate Fluctuations; Particle Filter; General Equilibrium; Konjunktur; Wirtschaftskrise; Geldpolitik; Finanzpolitik; Risiko; Neukeynesianische Makroökonomik; Allgemeines Gleichgewicht; Theorie; USA